Comprehensive Physiology 2012
DOI: 10.1002/cphy.c110052
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Transport in the Connecting Tubule and Cortical Collecting Duct

Abstract: The central goal of this overview article is to summarize recent findings in renal epithelial transport, focusing chiefly on the connecting tubule (CNT) and the cortical collecting duct (CCD). Mammalian CCD and CNT are involved in fine tuning of electrolyte and fluid balance through reabsorption and secretion. Specific transporters and channels mediate vectorial movements of water and solutes in these segments. Although only a small percent of the glomerular filtrate reaches the CNT and CCD, these segments are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
93
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 683 publications
(941 reference statements)
0
93
0
2
Order By: Relevance
“…Low plasma aldosterone reduces the ROMK by increased internalization and degradation of the channel and thus hyperkalaemia results. 9 Water reabsorption in the collecting duct through aquaporin mainly AQP2 in the apical and combination of AQP3 and AQP4 in the basolateral membranes respectively is the key event for maintenance of body water balance. The binding of vasopressin to its receptor (V 2 R) on basolateral membrane induces an increase in intracellular cAMP level which leads to activation of protein kinase A (PKA) and to phosphorylation of AQP2 channels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low plasma aldosterone reduces the ROMK by increased internalization and degradation of the channel and thus hyperkalaemia results. 9 Water reabsorption in the collecting duct through aquaporin mainly AQP2 in the apical and combination of AQP3 and AQP4 in the basolateral membranes respectively is the key event for maintenance of body water balance. The binding of vasopressin to its receptor (V 2 R) on basolateral membrane induces an increase in intracellular cAMP level which leads to activation of protein kinase A (PKA) and to phosphorylation of AQP2 channels.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of AQP2 channels stimulates its redistribution from the storage vesicles to the apical membrane rendering this membrane permeable to water reabsorption. 9 It has been suggested that the altered vasopressin regulation in diabetes mellitus, the increased insulin-induced potentiation of vasopressininduced AQP2 water channel's expression and the absorption of water from the GI tract due to slower stomach emptying may play a role in the association between diabetes mellitus and decreased serum Na + levels. 10 Some studies found opposite changes in serum Na+ and K+ levels viz.…”
Section: Discussionmentioning
confidence: 99%
“…Studies support both modes of regulation (39,40), and it seems likely that both are involved. SGK1 has been found to have effects on both P o and N, at least in part through inhibition of the E3 ubiquitin ligase NEDD4-2 (27, Figure 8.…”
Section: 4mentioning
confidence: 94%
“…IT IS GENERALLY RECOGNIZED that transport in the distal part of renal tubule, including the connecting tubule and the collecting duct, plays an important role in maintenance of whole body fluid homeostasis by shaping excretion rates of water and electrolytes with urine (32,40). This part contains two morphologically and functionally distinct cell populations, where principal cells (PC) mediate sodium and water reabsorption and secretion of potassium, and intercalated cells (IC) control acid-base balance and also participate in chloride reabsorption (40,44).…”
mentioning
confidence: 99%